Good jobs for inclusive growth in Central Asia and the South Caucasus regional report. - Capannelli, Giovanni
It reviews economic performance in the region and discusses prospects through 2030, introducing two growth scenarios related to the adoption of structural reforms for creating good jobs and inclusive growth. It also highlights the importance of adopting a full policy reform scenario.